2011
DOI: 10.11646/zootaxa.2855.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A subjective checklist of the Recent, free-living, non-marine Ostracoda (Crustacea)

Abstract: We present a subjective list of the Recent, free-living, non-marine ostracods species and genera of the world, with their distribution in the large zoogeographical regions, as well as a list of genera in their present hierarchical taxonomic position. Based on the recognised synonymies, there are at present about 2090 species in c. 209 genera. About half of all species occur in one family, the Cyprididae, which is especially common in the southern Hemisphere. We give three new names for extant homonyms (Cyprett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 15 publications
1
76
0
1
Order By: Relevance
“…Nevertheless, it has already been mentioned for Lake Los Juncos in the extant fauna (Gilbert 2012;Ramón Mercau et al 2012). Our study is the first record of T. lutaria in the Neotropical region (Martens and Savatenalinton 2011). There is no fossil record for this species in Patagonia therefore we might hypothesize a recent colonization.…”
Section: Ostracod Assemblagesmentioning
confidence: 72%
“…Nevertheless, it has already been mentioned for Lake Los Juncos in the extant fauna (Gilbert 2012;Ramón Mercau et al 2012). Our study is the first record of T. lutaria in the Neotropical region (Martens and Savatenalinton 2011). There is no fossil record for this species in Patagonia therefore we might hypothesize a recent colonization.…”
Section: Ostracod Assemblagesmentioning
confidence: 72%
“…Distribution.-This species is currently known from both the Palaearctic and the Oriental Regions (Martens & Savatenalinton, 2011). Previous records in China were restricted to the southern provinces (Yu et al, 2009), and this is the first record in the Palaearctic part of the country.…”
Section: Resultsmentioning
confidence: 93%
“…F Müller, 1776), Heterocypris incongruens (Ramdohr, 1808), Limnocythere inopinata (Baird, 1843), L. stationis Vâvra, 1891, Physocypria kraepelini G. W. Müller, 1903 and Plesiocypridopsis newtoni (Brady & Robertson, 1870)) have been recorded from various other parts of the world and display wide geographical distribution (Martens & Savatenalinton, 2011), some of them have been rarely, or not at all found in China before. For example, previous data indicated that P. kraepelini is widespread across Eurasia and North America (Meisch, 2000;Yu et ah, 2005Yu et ah, , 2010Martens & Savatenalinton, 2011), but it was not known from the Chinese territory north of Qinling Mountain (i.e., the Palaearctic part of China) until this study. The present study also presents the first reports of B. vittata, /.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the GBIF online resource only included 44 entocytherid occurrences hitherto, mainly corresponding to sampling localities of specimens preserved in Museum collec tions (e.g., National Museum of Natural History, Australian Museum). Another example of the reduced attention paid to the entocytherids by most ostracodologists are recent reviews of the world non-marine ostracod fauna that only con sider free-living ostracods (Martens et ah, 2008;Martens & Savatenalinton, 2011), disregarding this commensal group, or describing it in a very succinct way (e.g., Karanovic, 2012).…”
Section: Introductionmentioning
confidence: 99%